Whey protein isolate enrichment attenuates manganese-induced oxidative stress and neurotoxicity in Drosophila melanogaster: Relevance to Parkinson's disease. - Mohandas, G.; Rao, S.V.; Muralidhara; Rajini, P.S. (Biomedicine & Pharmacotherapy, 2017)
Currently, much emphasis is being laid on understanding the role of nutrition to alleviate neurodegenerative conditions. Here we employed a Drosophila model to test the hypothesis that Whey protein isolate (WPI) enrichment can attenuate Manganese (Mn) induced locomotor phenotype, oxidative stress and neurotoxicity. Mn exposure (0-30mM) to young (8-10d old) males/females and aged (30-35d old) males elicited a concentration-dependent temporal mortality and locomotor deficits. In general, females and aged males were more susceptible than young males. Mn exposure (5-15mM, 5d) among male flies, besides induction of oxidative stress (elevated levels of MDA and protein carbonyls with a concomitant decrease in glutathione levels), caused significant perturbations in the activities of antioxidant enzymes and mitochondrial complexes. In the co-exposure paradigm, WPI fortification (0.25-0.5%) markedly ameliorated Mn-induced locomotor phenotype, mortality, oxidative stress and restored the activity of the antioxidant enzymes, cholinergic function, and dopamine levels. In a satellite study, flies given prophylactic treatment (10d) with WPI were more resistant(evidenced by a lower incidence of mortality and locomotor deficits) to an acute MPP(+) challenge suggesting its potential to enhance survival pathways. Collectively, these data suggest the potential of WPI enrichment to attenuate Mn-induced toxic manifestations in the Drosophila model. Based on these findings, we propose that fortification of diet with WPI offers a useful approach to alleviate Mn-induced toxic manifestations and neuronal dysfunctions in humans, especially in occupational settings.